Upaya Meningkatkan Hasil Belajar Backhand Pada Materi Bulutangkis Menggunakan Triangle Games - Ni Putu Uliya Efriyanti; I Ketut Semarayasa; I Wayan Muliarta; I Made Satyawan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The purpose of this study was to determine how to improve backhand learning outcomes in badminton material using triangle games for students of class XI. The research method used in this study is to use the Classroom Action Research (CAR) method. This research was conducted at SMA, while the subjects of this research were students of class XI SMA which amounted to 42 people. For research instruments used in this study is an assessment based on three aspects, namely cognitive, affective and psychomotor. Based on the results of the study it is known that student learning outcomes have increased from pre-cycle to cycle II, namely, pre-cycle (24%), cycle I (64%), cycle II (100%). The conclusion of this study is that using triangle games can have a positive effect on the learning outcomes of backhand in badminton games for students of class XI SMA.   Keywords: Backhand, Badminton, Learning Outcome, Triangle Games